MHD Nanofluid Convection and Phase Change Dynamics in a Multi-Port Vented Cavity Equipped with a Sinusoidal PCM-Packed Bed System - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Mdpi, 2022)
In this study, impacts of using a sinusoidal shape encapsulated phase change material (PCM) packed bed (PB) system on the phase change and thermal performance are analyzed in multi-port vented cavity under a partially active magnetic field during hybrid nanoliquid convection. The current study is performed for different magnetic field strengths of domains (Hartmann number between 0 and 50), wave number (between 1 and 8), wave amplitude (between 0.01 H and 0.15 H), and nanoparticle loading (between 0 and 2%) by using the finite element method. The sinusoidal shape of the PCM-PB zone and varying its geometrical form are both found to affect the phase change process and thermal performance. When wave amplitude (Hp) rises from 0.01 H to 0.15 H, full phase change time (t-fr) increases by about 33% while average Nu increases by about 55%. When a partially active magnetic field is imposed at the highest value, up to 30.3% reduction in t-fr is obtained, while average Nu rises by about 9% at t = 18 min. The value of t-fr is reduced by about 15% while spatial average Nu rises by about 55% at the highest nanoparticle loading.
Keywords: vented cavity; partial magnetic field; packed bed; FEM; hybrid nanofluid; corrugated PCM